2011
DOI: 10.2527/jas.2010-3641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing lysine on further processed product characteristics from immunologically castrated male pigs

Abstract: The objective of this experiment was to determine if increasing lysine in the diets of immunologically castrated (IC) male pigs would affect further processed product characteristics when compared with physical castrates or entire males. Raw materials for this experiment were derived from a previous experiment evaluating carcass characteristics. Physical castrates, IC males, and entire males were assigned to 1 of 4 diet programs with increasing lysine in a step-down lysine inclusion program that culminated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
4
13
1
Order By: Relevance
“…The absence of significant differences in the percentage of SFA is in agreement with the results of Font i Furnols and Gispert (2009), Font-i-Furnols et al, (2012 and Boler, Kutzler, et al (2011), but is in contrast with Pauly et al (2009), who found a higher SFA proportion in surgically spayed than in immune-castrated males. Furthermore, the results of this study regarding the percentage of monounsaturated fatty acids (MUFA) are in concordance with the data of Pauly et al (2009), Boler, Clark, et al (2011) and Font-i-Furnols et al (2012. However, Font i Furnols and Gispert (2009) reported a higher amount of MUFA in the BF of surgically castrated males than in the BF of the immune-spayed ones.…”
Section: Fatty Acid Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…The absence of significant differences in the percentage of SFA is in agreement with the results of Font i Furnols and Gispert (2009), Font-i-Furnols et al, (2012 and Boler, Kutzler, et al (2011), but is in contrast with Pauly et al (2009), who found a higher SFA proportion in surgically spayed than in immune-castrated males. Furthermore, the results of this study regarding the percentage of monounsaturated fatty acids (MUFA) are in concordance with the data of Pauly et al (2009), Boler, Clark, et al (2011) and Font-i-Furnols et al (2012. However, Font i Furnols and Gispert (2009) reported a higher amount of MUFA in the BF of surgically castrated males than in the BF of the immune-spayed ones.…”
Section: Fatty Acid Profilesupporting
confidence: 92%
“…However, Font i Furnols and Gispert (2009) reported a higher amount of MUFA in the BF of surgically castrated males than in the BF of the immune-spayed ones. Finally, the lack of significant differences in the percentage of polyunsaturated fatty acids (PUFA) between the studied batches agrees with Boler, Clark, et al (2011) andFont-i-Furnols et al (2012), whereas Font i Furnols and Gispert (2009) andPauly et al (2009) reported higher PUFA content in immune-spayed with regard to surgically castrated males.…”
Section: Fatty Acid Profilesupporting
confidence: 74%
“…Bacon slice image analysis was conducted with a similar procedure described in Boler et al (2011). Slices were photographed as a set using a Canon Powershot SX20IS camera (Canon Inc., Melville, NY) at a standardized distance from the samples.…”
Section: Bacon Slice Lean Image Analysismentioning
confidence: 99%
“…Cooked yield was calculated from the following equation previously used by Boler et al (2011): Cooked yield ¼ Cooked weight Green weight  100: Bellies were individually placed in the slicer (TREIF USA Inc., Shelton, CT) and sliced to an approximate slice thickness of 24 slices per kg. Bacon was removed to maintain anatomical orientation.…”
Section: Bacon Slicingmentioning
confidence: 99%
“…Several studies have compared sensory characteristics of loins from IC barrows with other sexes (Hennessy, 2006;Font i Furnols et al, 2008, 2009Gispert et al, 2010) but none for bacon. Boar taint prevalence is potentially greater in bacon than in loins because of its 30 to 40% fat content (Scramlin et al, 2008;Boler et al, 2011) and the lipophilic nature of boar taint compounds (Claus et al, 1994;Babol et al, 1999). Therefore, the objectives were to compare slice characteristics and sensory attributes of bacon from IC barrows with bacon from other sexes using a trained sensory panel.…”
Section: Introductionmentioning
confidence: 99%